1995
DOI: 10.1074/jbc.270.48.28879
|View full text |Cite
|
Sign up to set email alerts
|

Brefeldin A Reversibly Inhibits the Assembly of ApoB Containing Lipoproteins in McA-RH7777 Cells

Abstract: BFA inhibited in a dose dependent way the assembly of apoB-48 very low density lipoprotein (VLDL) but allowed a normal rate of biosynthesis of the apolipoprotein and of the assembly of the dense ("high density lipoprotein (HDL)-like") apoB-48 particle (apoB-48 HDL). The inhibition of the assembly of apoB-48 VLDL occurred at BFA levels that allowed a major secretion of both transferrin and apoB-48 HDL. The assembly of apoB-100 containing lipoproteins was also inhibited by BFA but could be reactivated by a 30 -6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
72
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 45 publications
8
72
1
Order By: Relevance
“…As shown previously (7,8), BfA effectively blocked bulk TG incorporation into VLDL, which was confirmed here by its effect on B100-VLDL assembly within the microsomal lumen (Fig. 6C) (Fig.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…As shown previously (7,8), BfA effectively blocked bulk TG incorporation into VLDL, which was confirmed here by its effect on B100-VLDL assembly within the microsomal lumen (Fig. 6C) (Fig.…”
Section: Resultssupporting
confidence: 61%
“…Subsequently, bulk lipid is incorporated into the primordial particle to form a mature VLDL (7). Under certain conditions, such as insufficient lipid supply or treatment of a low dose of brefeldin A (BfA), the assembly/secretion of mature VLDL are impaired whereas those of small, dense particles remain normal (7,8). Apparently, multiple factors are involved for the maturation of VLDL.…”
mentioning
confidence: 99%
“…We have demonstrated that brefeldin A inhibits the major lipidation of apoB (9). However the exact localization of the brefeldin A-sensitive mechanism in the assembly pathway remains to be elucidated.…”
mentioning
confidence: 99%
“…The second step of VLDL assembly can be inhibited by brefeldin A (BFA) (6). Best known for inhibiting intracellular transport, BFA blocks a guanine nucleotide exchange (GDP for GTP) on ADP-ribosylation factor 1 (ARF-1) (9 -11), a member of the Ras superfamily of GTP-binding proteins.…”
mentioning
confidence: 99%
“…This step requires microsomal triglyceride transfer protein (for a review, see Ref. 5) and gives rise to a VLDL precursor that contains full-length apoB-100 (2-4, 6), which may be associated with the membrane of the ER (4,6,7). In the second step, the major amount of lipid is added to the core of the precursor particle to form VLDL (2).…”
mentioning
confidence: 99%